2023
DOI: 10.1007/s00394-023-03229-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between nutrient intake related to the one-carbon metabolism and colorectal cancer risk: a case–control study in the Basque Country

Abstract: Purpose Epidemiologic evidence for the association between methyl-donor nutrient intake and colorectal cancer (CRC) risk remains inconclusive. We aimed to examine the relationship between intake of vitamins of the B group, methionine, total choline and betaine and CRC risk, in a population from the CRC screening programme in the Basque Country. Design This observational study included 308 patients with CRC and 308 age- and sex-matched subjects as controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Concerning colon cancer, our results are consistent with prior research, suggesting a potential protective effect of choline intake. Earlier studies, including an Italian multicenter case‒control study [ 27 ] and recent observational research [ 11 ], have also shown an inverse relationship between choline intake and colorectal cancer risk. Nevertheless, divergent results must be acknowledged; for example, an Iranian case‒control study reported an elevated risk of colorectal cancer with increased choline intake [ 28 ], and a large cohort study tracking men over nearly 2 decades found no significant trend in colorectal cancer risk associated with choline intake [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning colon cancer, our results are consistent with prior research, suggesting a potential protective effect of choline intake. Earlier studies, including an Italian multicenter case‒control study [ 27 ] and recent observational research [ 11 ], have also shown an inverse relationship between choline intake and colorectal cancer risk. Nevertheless, divergent results must be acknowledged; for example, an Iranian case‒control study reported an elevated risk of colorectal cancer with increased choline intake [ 28 ], and a large cohort study tracking men over nearly 2 decades found no significant trend in colorectal cancer risk associated with choline intake [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of oncology, a meta-analysis of eleven scholarly articles indicated a possible inverse correlation between increased choline intake and overall cancer risk [ 10 ]. Nonetheless, there are contradictory results concerning colorectal cancer, with some studies revealing negative [ 11 ] or no significant relationships [ 12 ]. Elevated levels of plasma choline have been positively correlated with increased mortality risk among older adults in the United States [ 13 ] and among Chinese adults with hypertension [ 14 ].…”
Section: Introduction/backgroundmentioning
confidence: 99%